CASH HOLDINGS IN BRAZIL: A STUDY CONSIDERING THE EFFECTS OF FINANCIAL CONSTRAINTS AND THE ADOPTION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS - Manoel, Aviner Augusto Silva; Moraes, Marcelo Botelho da Costa (Revista Universo Contábil, 2019)
Firms use of internal and external sources to finance their activities. However, in the presence of imperfections in capital market, such as information asymmetry, agency problems and transaction costs, they may opt for one over another. In this sense, evidence obtained from previous studies suggests that cash holdings are more valuable for restricted companies than for unrestricted ones. Furthermore, the IFRS adoption is one of the most important subjects in recent accounting history. We analyze, in this article, the effects of financial constraints and the IFRS adoption on cash management in Brazil. For that, we used the Generalized Method of Moments (GMM) by dynamic panel data in order to explicitly consider the problems of endogeneity. The sample used comprises 219 public firms from 2000 to 2017. Our results indicate that, on average, the cash management of firms is influenced by its level of financial constraint. Financially constrained firms by size criteria and dividend-paying hold more cash than the smaller ones and non-dividend paying firms, respectively. We also verify a significant reduction in cash levels after the mandatory adoption of IFRS. Finally, our results reveal that firms’ leverage, profitability, growth opportunities, current liquidity, net working capital and short-term debt are important in determining cash holdings in Brazil.